EFEKTIVITAS PEMBELAJARAN MENULIS PUISI MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR PADA SISWA SMA KELAS X - Dea Puspita Sari; Teti Sobari; Restu Bias Primandhika (IKIP Siliwangi, 2026)
This study aims to analyze the effectiveness of the application of the PBL model assisted by image media in learning to write poetry for senior high school class X-A. The study began with the problems of students when they had difficulty learning to write poetry. In addition to problems with students, teachers mostly use the lecture method, which makes the lesson uninteresting so that students are less enthusiastic about learning, so that there is a lack of understanding in the material presented by the teacher. In order to overcome this, this study uses an innovative teaching model, namely the problem based learning model assisted by image media. This study uses a quantitative method with testing using pretest and posttest. The findings obtained from the number of cognitive and psychomotor values ​​​​of each pretest and posttest showed that many students still got scores below KKM, while the posttest results of 85% of students out of 33 people got scores above KKM. In addition, the application of the Problem Based Learning model assisted by Image Media managed to increase the value with an N-Gain result of 42.10%, which means that the data has a moderate category so that it is quite effective in improving poetry writing skills.